Splanchnic vein thrombosis predicts worse survival in patients with advanced pancreatic cancer. Issue 185 (January 2020) - Afzal, Amber; Suhong, Luo; Gage, Brian F.; Schoen, Martin W.; Carson, Kenneth; Thomas, Theodore; Sanfilippo, Kristen
Abstract: Introduction: Pancreatic cancer is a thrombogenic malignancy with nearly half of venous thrombotic events occurring in the splanchnic circulation. The effect of splanchnic vein thrombosis on mortality in pancreatic cancer is unknown. We studied the effect of splanchnic vein thrombosis on mortality in veterans with advanced pancreatic adenocarcinoma, and explored the association of anticoagulant therapy on mortality and hemorrhage. Methods: Using International Classification of Diseases (ICD) codes, we identified eligible patients and outcomes in the Veterans Health Administration database. Using Cox proportional hazards regression, we analyzed the association between splanchnic vein thrombosis and mortality among patients with advanced pancreatic cancer. We used propensity score inverse probability-of-treatment weighting to balance the groups who did and did not receive anticoagulation. To understand the role of anticoagulant therapy, we used Cox proportional hazards regression to analyze mortality and competing risk analysis to assess the risk of hemorrhage. Results: Of the patients with advanced pancreatic cancer (N = 6164), 122 developed splanchnic vein thrombosis. Splanchnic vein thrombosis was associated with a two-fold increase in mortality, aHR 2.02, 95% CI 1.65–2.47. The finding held true after restricting the analysis to patients undergoing treatment for pancreatic cancer, and after adjusting for immortal time bias by a 30-day landmark analysis. Anticoagulant therapy did not affect mortality (aHR 0.99, 95% CI 0.65–1.51), and increased the risk of hemorrhage (aHR 2.7, 95% CI 1.02–7.07). Conclusion: Splanchnic vein thrombosis predicts worse survival in patients with advanced pancreatic adenocarcinoma. Anticoagulant therapy may not mitigate this increased mortality, and increases the risk of hemorrhage. Highlights: Half of the venous thrombosis in pancreatic cancer occurs in splanchnic circulation. Splanchnic vein thrombosis predicts worse survival in patients with advanced pancreatic cancer. Anticoagulant therapy does not improve overall survival of these patients. Anticoagulant therapy increases the risk of hemorrhage.